Provenance of Mesozoic Meluhu sandstone and its implication to petroleum system in Meluhu area, southeast arm of Sulawesi - Surjono, Sugeng Sapto (IKATAN AHLI GEOLOGI INDONESIA (IAGI), 2018)
Meluhu Formation is siliciclastic sedimentary rocks located in southeast arm of Sulawesi. The formation was deposited simultaneously by the separation of the northern margin of the Australian continent in the Middle Triassic to Jurassic. The composition of sedimentary rocks was identified to determine the provenance of this formation including source rock and tectonic setting condition during the deposition of Meluhu Formation based on its composition. Furthermore, the results are utilized to interpret the paleogeographic setting and petroleum potential from identified source rock and tectonic setting. Eight samples of sandstones were selectively taken in the study area. Petrographic analysis was conducted to these samples by the point-counting method to obtain the detail the sandstone composition contained in rock samples. The triangular diagrams of QFL, QmFLt, and QpLvLs by Dickinson &Suczek (1979) were utilized to determine the provenance of Meluhu Formation by plotting of each mineral and lithic composition. The result of petrographic analysis of Meluhu sandstones shows 48.9% monocrystal quartz, 8.7% polycrystalline quartz, 2.5% plagioclase, 7.6% orthoclase, 15.5% sedimentary rock fragments, 4% metamorphic rock fragments, and 1.2% of other minerals. The plotted composition into triangular diagrams of Dickinson &Suczek (1979) suggests that the sedimentary constituents of Meluhu sandstones were derived from the collision orogen source. The source of sediments was derived from metamorphic basement showing a good indication for petroleum potential of the basin in this area. KeywordsMeluhu Formation, provenance, collision orogeny, metamorphic basement